Analisis Penggunaan Software Turnitin sebagai Alat Pendeteksi Plagiarisme - Rama Arief Permana; Diah Priharsari; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Plagiarism is an act that harms other people and educational institutions. Currently there is software that can prevent acts of plagiarism, especially in the academic field, namely turnitin software. Turnitin also adopts Artificial Intelligence technology where the system will check the text in uploaded files to find out if this file is affected by plagiarism or not. The use of turnitin software as a plagiarism detection tool raises various perceptions. Through the use of turnitin software, students who commit acts of plagiarism can be detected, so that the writing they write will be obtained and it will be known how much the percentage level of plagiarism is in the writing. While the lecturer's view is that the rules for writing papers that are declared plagiarism must have standards. This is done in order to reduce the level of plagiarism. Thus, this study aims to determine the differences between lecturers and students in viewing turnitin to avoid/detect plagiarism as well as things that are perceived as detrimental/beneficial in using turnitin. At the data collection stage it will be carried out in the lecturer room for lecturer sources and for student sources it will be done online. The interview method used is semi-structured interviews. The data obtained was analyzed using thematic analysis. The findings of this study resulted in two themes, namely the use of turnitin software by lecturers and student behavior regarding the use of turnitin software with 9 categories and 16 codes.